APLIKASI METODE KERNEL DALAM ESTIMASI FUNGSI HAZARD - Martadiputra, Bambang Avip Priatna (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2005)
Let T be a nonnegative random variable representing the lifetimes of individuals in some population. Let f(t) denote the probability density function of T and F(t) denote the distribution function of T, the hazard function of T defined as Â F(t) - 1Â  S(t)Â Â  whereS(t) f(t) h(t) ï½ ï½ If equation (1) integrated we have cumulative hazard function H (t).Â  This paper describes application of kernel method for estimation of hazard function h (.) based censoring data. And then we will show that the hazard estimator is unbiased asymptotically, consistent, and normal asymptotically.Â Key word: kernel methods, estimation hazard function.